2004
DOI: 10.1381/096089204323013622
|View full text |Cite
|
Sign up to set email alerts
|

Band Erosion with Gastric Cancer

Abstract: Adjustable gastric banding is a well-established procedure for the treatment of morbid obesity. We present a 62-year-old female who experienced the rare complication of intragastric band perforation due to a gastric adenocarcinoma localized at the site of gastric banding, 10 years after insertion of the band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 19 publications
0
17
0
1
Order By: Relevance
“…After restrictive bariatric operations, cancer has been reported in individual cases [1,3,[5][6][7][9][10][11]. A potential mechanism leading to cancer could be the prolonged contact of food containing exogenous carcinogenic factors in the gastric pouch.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After restrictive bariatric operations, cancer has been reported in individual cases [1,3,[5][6][7][9][10][11]. A potential mechanism leading to cancer could be the prolonged contact of food containing exogenous carcinogenic factors in the gastric pouch.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogenesis theories include chronic inflammatory changes leading to an intracellular dysregulation between reactive oxygen radicals and antioxidant substances. These changes are suspected to cause DNA mutations with consecutive gene regulation defects [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Pathologic study demonstrated a poorly differentiated adenocarcinoma with positive perigastric nodes and hepatic metastases.…”
Section: Gastric Cancer After Restrictive Operationsmentioning
confidence: 98%
“…Four cases of adenocarcinoma of the stomach have been reported after VBG. Two occurred in the gastric pouch, at 2 and 15 years after surgery 11,12 A third lesion appeared in the distal stomach 6 years after VBG, 13 while the fourth patient was diagnosed with a linitis plastica of the entire stomach 13 years after VBG 14 A fifth case of gastric pouch cancer was described 10 years after adjustable gastric banding in a 62-year-old lady 15 Most of the cases were diagnosed with advanced disease, while a non-specific history of epigastric pain, nausea and vomiting had already been present for considerable time before the diagnosis was made.…”
Section: Figure 2 Gist Spindle Cell Tumor With Focal Collagen Deposmentioning
confidence: 99%